Exploring New Territories: New Records and Occurrence Confirmation of Two Caridean Shrimps in Brazil - Lucas Rezende Penido Paschoal; Caio Santos Nogueira; Fernando José Zara (Arthropoda)
Here, we confirm the presence of two species of caridean shrimps for the first time in Brazil: Latreutes parvulus and Ambidexter cochensis. During active samplings conducted in December 2023, April 2024 and September 2024 on the rocky shore of Prainha da USP (Ubatuba municipality, São Paulo state, southeastern Brazil), we captured five ovigerous females of L. parvulus and fifteen individuals of A. cochensis (five males, three non-ovigerous females and seven ovigerous females). All the females of L. parvulus exhibited eyestalks with small, truncated processes separating the cornea from the stalk, a unique feature of this species. On the other hand, all specimens of A. cochensis exhibited a unique combination of characteristics: a rostrum with an apex bifid, a stylocerite bearing a lateral spinule and a transverse row of setae between the anterior pair of spines, and three longitudinal rows of setae on the telson. Also, males of A. cochensis had the tip of their appendix masculina armed with four simple apical setae and another two setae positioned below them. All analyzed shrimps had fully developed gametes in their reproductive systems, indicating breeding populations in this area. This is the first record of L. parvulus on the Atlantic coast of South America and a new meridional distribution limit for A. cochensis.